Neurology and clinical neuroanatomy on the move - Tate, Matthew, 1987-; Cooper-Knock, Johnathan, 1982-; Hunter, Zoe, 1985-; Wood, Elizabeth, 1986-; tate ,Malthew (New York: CRC Press, Taylor & Francis Group, 2015)
"The Medicine on the Move series provides fully flexible access to subjects across the curriculum in a unique combination of print and mobile formats ideal for the busy medical student and junior doctor. No matter what your learning style, whether you are studying a subject for the first time or revisiting it during exam preparation, Medicine on the Move will give you the support you need. This innovative print and app package will help you to connect with the topics of neurology and clinical neuroanatomy, to learn, understand and enjoy them, and to cement your knowledge in preparation for exams and future clinical practice. By using this resource in print or as an app, you really will experience the opportunity to learn medicine on the move"--
Includes index.
Keywords: Nervous System Diseases -- Examination Questions; Nervous System -- anatomy & histology -- Examination Questions